Preferensi Pengunjung Taman di Kota Malang Terhadap Fasilitas Taman Pasca Pandemi Covid-19 - Dian Kartika Santoso; Yudhistira Adit Dewanto; Kholishotunni’amillah; Siti Hazar Rachmawati; Risnawati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: Park Visitor Preferences On Park Facilities In Malang City Post-Covid-19 Pandemic The end of the Covid-19 Pandemic has made people return to their activities in public open spaces. After the post-Covid-19 pandemic, garden facilities are one of the essential things in an Open Green Space. This parking facility must comply with the ongoing New Normal Standards. Urban park in Malang needs to be measured to explore user preferences for park facilities after the Covid-19 pandemic. The analytical method used is a descriptive quantitative approach. Data collection was carried out through a survey using a questionnaire with a Likert scale. The results obtained from this study were that there was no change in visitor preferences before and after Covid-19. visitor preferences for park facilities in Malang City found that for hygiene & health facilities, the most needed are toilets, hand washing areas and trash cans, as for the most needed security facilities, namely security posts and fences. The most needed supporting facilities are seats, sports facilities and parking lots.